2010
DOI: 10.1016/j.biomaterials.2010.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Dual delivery of VEGF and MCP-1 to support endothelial cell transplantation for therapeutic vascularization

Abstract: Transplantation of endothelial cells (EC) for therapeutic vascularization is a promising approach in tissue engineering but has yet to be proven effective in clinical trials. This cell-based therapy is hindered by significant apoptosis of EC upon transplantation as well as poor recruitment of host mural cells to stabilize nascent vessels. Here, we address these deficiencies by augmenting endothelial cell transplantation with dual delivery of vascular endothelial growth factor (VEGF) – to improve survival of tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(48 citation statements)
references
References 53 publications
(86 reference statements)
0
47
0
Order By: Relevance
“…23 (ii) Angiogenic growth factor delivery. 24,25 (iii) In vitro engineering a prevascularized tissue before implantation. 26,27 It is well accepted that the third strategy is the only viable solution for larger volume tissues and rapid vascularization.…”
Section: Discussionmentioning
confidence: 99%
“…23 (ii) Angiogenic growth factor delivery. 24,25 (iii) In vitro engineering a prevascularized tissue before implantation. 26,27 It is well accepted that the third strategy is the only viable solution for larger volume tissues and rapid vascularization.…”
Section: Discussionmentioning
confidence: 99%
“…29 They secrete the ECM and a number of growth factors, in particular vascular endothelial growth factor (VEGF), 28,29 which has a key role in the promotion of angiogenesis, 30,31 and acts as a mitogen, survival factor, and chemoattractant for endothelial cells (ECs). [32][33][34][35] Since vascularization is a prerequisite for the survival and function of any transplanted or recruited cells, this feature is of great interest. VEGF is also known to play other key roles in cardiac repair.…”
Section: Introductionmentioning
confidence: 99%
“…(Kuliszewski et al, 2011;Yu et al, 2009) Dual delivery of VEGF and MCP-1 from alginate microbeads has been shown to support EC transplantation, with VEGF improving survival of transplanted ECs and MCP-1 inducing MCs recruitment. (Jay et al, 2010) A similar effect was observed when codelivering FGF-2 and granulocyte-colony stimulating factor (G-CSF) with bone marrow cells transplanted in a rodent model of critical limb ischemia. While FGF-2 directs EC migration and proliferation, G-CSF promotes the homing of bone marrow stem cells (in particular EPCs) to the ischemic site.…”
Section: Cell Therapiesmentioning
confidence: 76%
“…Subcutaneous implantation of scaffold materials is a commonly used method to evaluate protein, gene or cell therapies. (Jay et al, 2010;Shea et al, 1999;Tengood et al, 2010) Growth factors, genes or cells can be embedded a matrix material, which will then be implanted subcutaneously to animals as a "plug". The presence of therapeutic agents will affect local neovascularization and tissue invasion into the material.…”
Section: In Vivo Modelsmentioning
confidence: 99%